Pesantren sebagai Subkultur dan Tantangan di Era Post Truth: Analisis Framing Kasus Trans7 terhadap Pesantren Lirboyo - Femila Sari, Nur Rovida; Ulfa, Marya; Hasanah, Siti Waqi’atul; Hamidah, Lilik (Indonesian Journal of Humanities and Social Sciences, 2025)
In the post-truth era, circulating information does not guarantee the truth of the facts but tends to accept information based on emotions. The purpose of this study is to analyze the concept of post-truth, its impact on da'wah, the challenges faced, and strategies for overcoming them. This study uses a qualitative method with a literature study approach. Data were collected through journals, books, and other supporting sources. Seen from the case example of the broadcast of the program "Xpose Uncersored" Trans7 about the Lirboyo Islamic Boarding School which has become a pro and con in society. The broadcast contained a provocative narrative that sparked polemics in society, even more than 137 thousand social media users reacted through #BoycottTrans7 as a form of rejection. This case study was analyzed using N. Entman's Framing Theory. The novelty of the study lies in several approaches that are rarely used together, namely post-truth analysis, media framing, and the study of Islamic boarding school subculture. The research data includes: the narrative of the Trans7 broadcast, public responses on social media, as well as responses from Islamic boarding schools and institutions through news circulating in the community. Research results show that the post-truth era can present serious challenges for da'wah, such as the spread of instant information, disinformation, and religious hoaxes, as well as low media literacy. Addressing these challenges requires a comprehensive strategy encompassing a progressive Islamic approach, developing digital literacy, and clarifying the facts. The Trans7 case demonstrates that narratives shape public opinion without thorough verification, which can be misleading.